Non-linear statistical models on estimation of maximum size of Tor putitora (Hamilton) in different aquatic environments - Singh, N Okendro; Joshi, C B; Paul, A K (Indian Journal of Fisheries, 2011)
Tor putitora is one of the most important coldwater fish species. The population of this fish species has declined sharply inthe recent past and is threatened with multifaceted dangers. As the size of fish plays an important role in fish stockassessment, in the present investigation, an attempt has been made to estimate the maximum size of Tor putitora indifferent aquatic environments by using nonlinear statistical models. We can expect a maximum length of approximately3097 mm and 2994 mm for Tor putitora in the aquatic environments of Kumaun lakes and Gobindsagar reservoir respectively.It is seen that the estimated maximum size of Tor putitora in both environments are well acceptable in view of thereported maximum sizes in India and abroad.